Functionalized Flexible Soft Polymer Optical Fibers for Laser Photomedicine. Issue 3 (28th December 2017) - Jiang, Nan; Ahmed, Rajib; Rifat, Ahmmed A.; Guo, Jingjing; Yin, Yixia; Montelongo, Yunuen; Butt, Haider; Yetisen, Ali K.
Abstract: Optical waveguides allow propagating light through biological tissue in optogenetics and photomedicine applications. However, achieving efficient light delivery to deep tissues for long‐term implantation has been limited with solid‐state optical fibers. Here, a method is created to rapidly fabricate flexible, functionalized soft polymer optical fibers (SPOFs) coupled with silica fibers. A step‐index core/cladded poly(acrylamide‐ co ‐poly(ethylene glycol) diacrylate)/Ca alginate SPOF is fabricated through free‐radical polymerization in a mold. The SPOF is integrated with a solid‐state silica fiber coupler for efficient light delivery. The cladded SPOF shows ≈1.5‐fold increase in light propagation compared to the noncladded fiber. The optical loss of the SPOF is measured as 0.6 dB cm −1 at the bending angle of 70° and 0.28 dB cm −1 through a phantom tissue. The SPOF (inner Ø = 200 µm) integrated with a 21 gauge needle (inner Ø = 514 µm) is inserted within a porcine tissue. The intensity of light decreases ≈60%, as the SPOF is implanted as deep as 2 cm. Doped with fluorescent dye and gold nanoparticles, the SPOF fiber exhibits yellow‐red and red illumination. Living cells can also be incorporated within the SPOF with viability. The flexible SPOFs may have applications in photodynamic light therapy, optical biosensors, and photomedicine. Abstract : Soft polymer optical fibers coupled with solid‐state fibers are utilized for efficient light propagation within biological tissues. The step‐index optical fibers have poly(acrylamide‐ co ‐poly(ethylene glycol) diacrylate) as cores, and calcium alginate as claddings. Polymer optical fibers are functionalized with fluorophores, nanoparticles, and living cells, which may allow clinical applications in laser photomedicine.